Integrating Bayesian Inference with Scanning Probe Experiments for Robust Identification of Surface Adsorbate Configurations. (13th May 2021) - Järvi, Jari; Alldritt, Benjamin; Krejčí, Ondřej; Todorović, Milica; Liljeroth, Peter; Rinke, Patrick
Abstract: Controlling the properties of organic/inorganic materials requires detailed knowledge of their molecular adsorption geometries. This is often unattainable, even with current state‐of‐the‐art tools. Visualizing the structure of complex non‐planar adsorbates with atomic force microscopy (AFM) is challenging, and identifying it computationally is intractable with conventional structure search. In this fresh approach, cross‐disciplinary tools are integrated for a robust and automated identification of 3D adsorbate configurations. Bayesian optimization is employed with first‐principles simulations for accurate and unbiased structure inference of multiple adsorbates. The corresponding AFM simulations then allow fingerprinting adsorbate structures that appear in AFM experimental images. In the instance of bulky (1 S )‐camphor adsorbed on the Cu(111) surface, three matching AFM image contrasts are found, which allow correlating experimental image features to distinct cases of molecular adsorption. Abstract : Artificial intelligence (AI) enhanced ab initio structure search is combined with atomic force microscopy simulations (SIM) and experiments (EXP) to detect configurations of bulky 3D adsorbates. Bayesian inference is employed to identify distinct stable adsorption configurations of (1 S )‐camphor on the Cu(111) surface, followed by SIM‐EXP image feature matching to fingerprint multiple experimental structures at the same time.